Autonomic Function Recovery and Physical Activity Levels in Post-COVID-19 Young Adults after Immunization: An Observational Follow-Up Case-Control Study - Freire, Ana Paula Coelho Figueira [UNESP]; Amin, Shaan; Lira, Fabio Santos [UNESP]; Morano, Ana Elisa von Ah [UNESP]; Pereira, Telmo; Coelho-E-Silva, Manuel-João; Caseiro, Armando; Christofaro, Diego Giulliano Destro [UNESP]; Dos Santos, Vanessa Ribeiro [UNESP]; Júnior, Osmar Marchioto [UNESP]; Pinho, Ricardo Aurino; Silva, Bruna Spolador de Alencar [UNESP] (MDPI, 2023)
Coronavirus disease 2019 (COVID-19) has detrimental multi-system consequences. Symptoms may appear during the acute phase of infection, but the literature on long-term recovery of young adults after mild to moderate infection is lacking. Heart rate variability (HRV) allows for the observation of autonomic nervous system (ANS) modulation post-SARS-CoV-2 infection. Since physical activity (PA) can help improve ANS modulation, investigating factors that can influence HRV outcomes after COVID-19 is essential to advancements in care and intervention strategies. Clinicians may use this research to aid in the development of non-medication interventions. At baseline, 18 control (CT) and 20 post-COVID-19 (PCOV) participants were observed where general anamnesis was performed, followed by HRV and PA assessment. Thus, 10 CT and 7 PCOV subjects returned for follow-up (FU) evaluation 6 weeks after complete immunization (two doses) and assessments were repeated. Over the follow-up period, a decrease in sympathetic (SNS) activity (mean heart rate: p = 0.0024, CI = −24.67–−3.26; SNS index: p = 0.0068, CI = −2.50–−0.32) and increase in parasympathetic (PNS) activity (mean RR: p = 0.0097, CI = 33.72–225.51; PNS index: p = 0.0091, CI = −0.20–1.47) were observed. At follow-up, HRV was not different between groups (p > 0.05). Additionally, no differences were observed in PA between moments and groups. This study provides evidence of ANS recovery after SARS-CoV-2 insult in young adults over a follow-up period, independent of changes in PA.
Keywords: autonomic nervous system; communicable diseases; COVID-19; COVID-19 vaccination; exercise; parasympathetic nervous system; post-acute sequelae of COVID-19; SARS-CoV-2; sympathetic nervous system